Pembuatan dan Mikroenkapsulasi Ekstrak Etanol Biji Jinten Hitam Pahit (Nigella sativa Linn.) - Sugindro, Sugindro; Mardliyati, Etik; Djajadisastra, Joshita (Majalah Ilmu Kefarmasian, 2008)
The aim of this study is to convert Nigella sativa black seed extract from liquid phase into solid phase by microencapsulation using spray drying method. The benefits hoped from this research are obtaining the dry extract to be formulated into pharmaceutical variable dosage forms in order to increase the usefulness and variability products of Nigella sativa black seed extract. The spray drying method was done by adding Nigella sativa black extract into the gum arabic and maltodextrin solution. The evaluation of microencapsulated extract is including drug content, encapsulation efficiency, flow properties, compressibility, angle of repose, moisture content, particel size distribu-tion and microstructure of microcapsules. The result showed that microencapsula-tion of Nigella sativa black seed extract can be produced by spray drying method. The highest microencapsulation efficiency is at the coating solution concentration of 20% (gum arabic : maltodextrin = 50 : 50) and Nigella sativa black extract percentage of 30%.